Feasibility of aortic valve planimetry at 7 T ultrahigh field MRI: Comparison to aortic valve MRI at 3 T and 1.5 T. (2018) - Goebel, Juliane; Nensa, Felix; Schemuth, Haemi P.; Maderwald, Stefan; Schlosser, Thomas; Orzada, Stephan; Rietsch, Stefan; Quick, Harald H.; Nassenstein, Kai
Abstract: Introduction: This study examined the feasibility of aortic valve planimetry at 7 T ultrahigh field MRI in intraindividual comparison to 3 T and 1.5 T MRI. Material and methods: Aortic valves of eleven healthy volunteers (mean age, 26.4 years) were examined on a 7 T, 3 T, and 1.5 T MR system using FLASH and TrueFISP sequences. Two experienced radiologists evaluated overall image quality, the presence of artefacts, tissue contrast ratios, identifiability, and image details of the aortic valve opening area (AVOA). Furthermore, AVOA was quantified twice by reader 1 and once by reader 2. Correlation analysis between artefact severity and employed magnetic field strength was performed by modified Fisher's exac t -test. Paired t -test was used to analyse for AVOA differences, and Bland-Altman plots were used to analyse AVOA intra-rater and inter-rater variability. Results: Aortic valve imaging at 7 T, 3 T, and 1.5 T with using FLASH was less hampered by artefacts than TrueFISP imaging at 3 T and 1.5 T. Tissue contrast and image details were rated best at 7 T. AVOA was measured slightly smaller at 7 T compared to 3 T (TrueFISP, p-value = 0.057; FLASH, p-value = 0.016) and 1.5 T (TrueFISP, p-value = 0.029; FLASH, p-value = 0.018). Intra-rater and inter-rater variability of AVOA tended to be slightly smaller at 7 T than at 3 T and 1.5 T. Conclusion: Aortic valve planimetry at 7 T ultrahigh field MRI is technically feasible and in healthy volunteers offers an improved tissue contrast and a slightly better reproducibility than MR planimetry at 1.5 T and 3 T.